2021
DOI: 10.1007/s10517-021-05371-5
|View full text |Cite
|
Sign up to set email alerts
|

Secretome of Mesenchymal Bone Marrow Stem Cells: Is It Immunosuppressive or Proinflammatory?

Abstract: Mesenchymal stem cells (MSC) are characterized by tolerogenic potential and therefore, are used in the treatment of autoimmune diseases such as graft-versus-host disease (GVHD) reactions after allogeneic hematopoietic cell transplantation to improve the transplant functions, as well as for the therapy and prevention of cytokine storm in COVID-19 patients and some other conditions. However, MSC can exhibit proinflammatory activity, which causes risks for their clinical use. We studied the cytokine profile of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
1
6
0
3
Order By: Relevance
“…In IVDD, BMSCs are the most studied intervention among MSCs from other sources. Cytokine profiling of BMSCs, however, revealed intensive production of proinflammatory cytokines IL-6 and IL-8 (Kiselevskii et al, 2021), which may contradict the report that MSCs induce anti-inflammatory effects (Marimuthu and Pushpa Rani, 2021). In addition, BMSCs aid the expression of vascular endothelial growth factor (VEGF) to promote angiogenesis under hypoxic conditions (Archacka et al, 2021).…”
Section: Bmscsmentioning
confidence: 90%
“…In IVDD, BMSCs are the most studied intervention among MSCs from other sources. Cytokine profiling of BMSCs, however, revealed intensive production of proinflammatory cytokines IL-6 and IL-8 (Kiselevskii et al, 2021), which may contradict the report that MSCs induce anti-inflammatory effects (Marimuthu and Pushpa Rani, 2021). In addition, BMSCs aid the expression of vascular endothelial growth factor (VEGF) to promote angiogenesis under hypoxic conditions (Archacka et al, 2021).…”
Section: Bmscsmentioning
confidence: 90%
“…The cytokine secretion profiles of MSCs derived from different sources and cultured under different conditions still contain contradictions. Some studies have reported that MSCs do not secrete cytokines such as IL-4 and IL-10 under normal conditions [ 38 ] and can detect only inflammatory conditions and the presence of cytokines [ 39 ]. However, studies showing that amniotic fluid and adipose tissue-derived MSCs secrete cytokines such as IL-4, IL-6, and IL-10 are also available in the literature [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…С появлением и развитием тканевой инженерии ГГ стали использовать для восстановления и регенерации различных тканей и органов [1]. Мезенхимальные мультипотентные (стволовые) стромальные клетки (ММСК) применяют для регенерации тканей, лечения и профилактики цитокинового шторма при COVID-19 и реакции «трансплантат против хозяина», а также для стимуляции гемопоэза при аллогенной трансплантации стволовых гемопоэтических клеток [2][3][4][5]. В отличие от рутинного культивирования использование ГГ позволяет создавать 3D-скаффолды, заселенные ММСК, что дает возможность локализовать эти клетки в области тканей-мишеней [6].…”
Section: Introductionunclassified